Association between climate change and patient health outcomes: a mixed-methods systematic review - Jana Turzáková; Dominika Kohanová; Andrea Solgajová; Tomáš Sollár (BMC Nursing, 2024)
Abstract Introduction Climate change poses significant threats to the environment, biodiversity, and socioeconomic stability worldwide. Its impact on human health, particularly within healthcare systems, is growing in concern. Nurses, as front-line healthcare workers, play a crucial role in addressing climate-related health risks. However, there is a gap in understanding nursing perspectives on climate change and its implications for patient health outcomes. Aim To synthesize empirical evidence on the association between climate change and patient health outcomes from a nursing perspective. Methods A mixed-methods systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The search was carried out in January 2024 in six scientific databases including CINAHL, PubMed, Scopus, ProQuest, Web of Science, and OVID Nursing. Studies focusing on climate change and patient health outcomes from a nursing perspective were included. Data extraction, quality appraisal, and synthesis were performed systematically. Results The systematic review included 18 studies of a mainly quantitative nature. Three main themes emerged as follows: Climate Healthcare Interplay; Future Nurses as Agents of Change; and Navigating Sustainability Challenges in Nursing. These themes highlighted nurses’ awareness of the interrelation between climate and health, the need for environmental education in nursing, and the challenges that hinder sustainable nursing practices. Conclusion This review underscores the importance of integrating climate change topics into nursing education and fostering organizational support for sustainable nursing practices. Addressing these challenges is essential for nurses to mitigate the health risks posed by climate change effectively.